2023
DOI: 10.3390/rs15030586
|View full text |Cite
|
Sign up to set email alerts
|

Cotton Fiber Quality Estimation Based on Machine Learning Using Time Series UAV Remote Sensing Data

Abstract: As an important factor determining the competitiveness of raw cotton, cotton fiber quality has received more and more attention. The results of traditional detection methods are accurate, but the sampling cost is high and has a hysteresis, which makes it difficult to measure cotton fiber quality parameters in real time and at a large scale. The purpose of this study is to use time-series UAV (Unmanned Aerial Vehicle) multispectral and RGB remote sensing images combined with machine learning to model four main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…observed that varying fertilizer levels and planting systems did not significantly affect fiber length. Since quality parameters are primarily determined by genetics and minimally influenced by management practices, there were no significant differences, as supported byGacche and Gokhale (2018);Xu et al (2023).…”
mentioning
confidence: 69%
“…observed that varying fertilizer levels and planting systems did not significantly affect fiber length. Since quality parameters are primarily determined by genetics and minimally influenced by management practices, there were no significant differences, as supported byGacche and Gokhale (2018);Xu et al (2023).…”
mentioning
confidence: 69%
“…Chevrollier et al explore how dynamic capabilities, such as sensing and seizing, can support sustainable strategic orientations in the apparel industry [22]. In line with the proposed topic, Xu et al presented an article that combines UAV (Unmanned Aerial Vehicle) multispectral and RGB (Red, Green, Blue) remote sensing and machine learning to model cotton fiber quality indicators, achieving improved prediction accuracy compared to traditional methods [23]. It provides a non-invasive and scalable approach for predicting cotton fiber quality, aiding variety breeding and commercial decision-making in the industry.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…In the case of multispectral analysis, as proposed here, drones require dedicated multispectral cameras to capture the required images. Multispectral cameras are instrumental in object classification [20][21][22] and pattern analysis [23], and when combined with advanced deep learning algorithms [1,[24][25][26][27][28][29], they can provide substantial data for comprehensive analysis when used effectively.…”
Section: Related Workmentioning
confidence: 99%